Novitates neocaledonicae I: An additionnal new species of Planchonella (Sapotaceae) endemic to the Roches de la Ouaième - Munzinger, Jerome (Phytotaxa, 2015)
A new species of Planchonella, endemic to the Roches de la Ouaième in northeastern New Caledonia, is described and illustrated. Planchonella ulfii morphologically resembles P. roseoloba, while molecular data indicate a closer relation to P. minutiflora and P. koumaciensis, with all three species belonging to a clade characterized by ridged fruits. The new species brings the total for the genus to 37 species in New Caledonia, 36 of which are endemic to the archipelago. With a single known population comprising 10 individuals, a preliminary risk of extinction assessment using the IUCN Red List criteria indicates that it is Critically Endangered due to risk of fire faced by the shrubby vegetation found of the summit crest of the Roches de la Ouaième. The level of micro-endemism found at this site is discussed.